Sustainable development research at universities in the United Kingdom : approaches, methods and projects - Leal Filho, Walter (Springer, 2017)
This book gathers inputs from a variety of researchers in the field of sustainable development in the widest sense across the UK, from business and economics, to arts and fashion, administration, environment and media studies. The book also describes research, curriculum innovation, and campus greening in a comprehensive way. Many universities in the United Kingdom are currently engaged in high-quality research on matters related to sustainable development. Yet there are relatively few publications that provide a multidisciplinary overview of these efforts and projects, and in which researchers from across the spectrum of the natural and social sciences have the opportunity to present their research methods, the results of their empirical research, or exchange ideas about on-going and future research initiatives focusing on sustainable development. Addressing this important gap in the literature, this book contributes to the further development of this rapidly growing field in the United Kingdom and beyond.
Keywords: Sustainable development -- Research -- Great Britain.; Great Britain.; elektronické knihy; electronic books